GAMBARAN TINGKAT PENGETAHUAN IBU DAN PEMBERIAN MAKANAN TAMBAHAN KEPADA BALITA UMUR 6-12 BULAN DI GAMPONG BLANG GANDAI KECAMATAN JEUMPA KABUPATEN BIREUEN - Asrita .; Siti Maryam; Rahmawati . (Program Studi Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Almuslim, 2013)
Each family wants to have a healthy and intelligent child to be grown up as a worthwhile person for parents and nation in the future. The purpose of this study was to describe the level of mother’s knowledge and supplementary feeding for infants aged 6-12 months in Gampong Blang Gandai, Jeumpa, Bireuen. The approach used in this study was quantitative approach, whereas the type of research is survey research. The research was conducted on 15 to 23 July, 2013. The results showed that the level of mother's knowledge about food additives majority was good (72.72%) and interest of the mother to give extra food was also good (81.81%). Information about food additives as well as supplementary feeding in children were in good level in amount of 77.27% and 90.90%. Keywords: supplementary feeding, infants, Gampong Blang Gandai